THE INFLUENCE OF AI IMPLEMENTATION IN LOCAL GOVERNMENT INFORMATION SYSTEMS ON THE EFFECTIVENESS OF PUBLIC SERVICE DELIVERY IN INDONESIA - Dhea Revina Shabila; Joni Pratikno; Abdul Wahid; Ariani; Tetra Hidayati (CV. RADJA PUBLIKA, 2025)
The rapid development of technology has brought significant changes in various aspects of life, including governance. One of the innovations that has been widely adopted is Artificial Intelligence (AI), which plays a crucial role in enhancing the efficiency, effectiveness, and quality of public services. The Indonesian government itself has made efforts to utilize this technology through the Electronic-Based Government System (SPBE) policy, which is regulated in Presidential Decree No. 95 of 2018. The implementation of AI in the public sector is expected to support the vision of “Golden Indonesia 2045” by creating a more adaptive, transparent, and accountable bureaucracy. However, the implementation of AI in government is not without challenges, such as bureaucratic complexity, limited digital infrastructure, and low levels of technological literacy among state officials. Therefore, a comprehensive and sustainable strategy is needed, including the development of human resource competencies and the application of ethical policies aligned with the values of Pancasila and the AI principles agreed upon in the G20 forum. This study aims to analyze the impact of AI implementation in local government information systems on the effectiveness of public service delivery in Indonesia. Additionally, this research also explores the extent to which AI implementation can drive organizational development in government agencies with complex hierarchical structures. The findings of this study are expected to provide both theoretical and practical contributions to strengthening technology-based governance in Indonesia.